2009
DOI: 10.33584/jnzg.2009.71.2757
|View full text |Cite
|
Sign up to set email alerts
|

The performance of pasture mixes containing 'Ceres Tonic' plantain (Plantago lanceolata) in Northland

Abstract: Over the last 10-15 years 'Ceres Tonic' plantain (Plantago lanceolata) has been added to many ryegrass/ white clover pastures in Northland. From 2001 to 2009, measurements were undertaken monthly in six locations throughout Northland to record the dry matter contribution of 'Tonic' plantain in mixes relative to perennial ryegrass-based pasture, using pasture cages in paired paddocks. Keywords: pasture mixes, dry matter production, seasonal distribution of dry matter, persistence

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…Mixed pastures including herbs like plantain or chicory tend to be more productive improving dry matter distribution in comparison with typical perennial ryegrass-based pastures used in New Zealand (Moorhead & Piggot 2009), and increasing lamb growth rates in late summer and autumn (Golding et al 2008).…”
Section: Herbage Productionmentioning
confidence: 99%
“…Mixed pastures including herbs like plantain or chicory tend to be more productive improving dry matter distribution in comparison with typical perennial ryegrass-based pastures used in New Zealand (Moorhead & Piggot 2009), and increasing lamb growth rates in late summer and autumn (Golding et al 2008).…”
Section: Herbage Productionmentioning
confidence: 99%
“…Yield advantages occur because chicory and plantain are highly productive and drought tolerant, with extensive root systems (Stewart 1996;Li & Kemp 2005). The deep-rootedness enables greater nutrient and moisture capture lower in the soil profile than is possible with more shallow-rooted species such as perennial ryegrass and white clover, demonstrated for example in studies of chicory and plantain (Stewart 1996;Sanderson & Elwinger 2004;Li & Kemp 2005;Høgh-Jensen et al 2006;Moorhead & Piggot 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Chicory (Cichorium intybus) is a tap-rooted herb that has high growth rates in late spring and summer (Hare et al 1990). Moorhead & Piggot (2009) showed that adding the herb plantain (Plantago lanceolata) to perennial ryegrass pasture mixes increased DM production by 1.8 t DM/ha in summer. Sudan grass (Sorghum sudanense) is a cereal forage that is capable of yielding 12.4 t DM/ha over the 4 months from December to March (Silungwe 2011).…”
Section: Introductionmentioning
confidence: 99%